The possibility of using the regranulate of a biodegradable polymer blend based on polylactic acid and polyhydroxybutyrate in FDM 3D printing technology - Slávka Hlaváčiková; Leona Omaníková; Vojtech Horváth; Pavol Alexy; Viera Jančovičová; Andrej Baco; Mária Mikolajová; Mária Fogašová; Katarína Tomanová; Jozef Feranc; Michal Ďurfina; Přemysl Menčík; et al. (Results in Materials, 2024)
The study's main objective is the possible application of regranulate based on PLA and PHB bioplastics in the FDM 3D printing technique. The idea of using regranulate in the tested PLA/PHB biodegradable polymer blend can help to reduce the amount of plastic waste produced after defective or unwanted 3D printing from these types of materials suitable for 3D printing or after the industrial production of filaments with inadequate geometric parameters, which may help to economize raw material resources and, ultimately, lower the cost of studied polymer materials producing. The regranulate was added to the non-recycled biodegradable polymer blend with the same chemical composition in two different processes for making the filament for 3D printing. Based on testing the processing and utility properties of the processed regranulate materials, it was found that the regranulate partially degrades during multiple processing and thereby reduces the average molar mass and viscosity of the tested material during its processing. However, it was proven that despite the reduction of molecular characteristics after regranulate additions, it was possible to prepare the filaments by both investigated technologies of the regranulate addition and subsequently, it was possible to print such filaments using FDM 3D printing technology, even when the polymer blend contained a high content of regranulate. It was also proven that PLA/PHB materials containing regranulate exhibit comparable thermophysical and strength characteristics to the virgin PLA/PHB polymer blend.